Research into the fire properties of wood products most frequently used in construction - Mačiulaitis, Romualdas; Praniauskas, Vladas; Yakovlev, Grigory (Journal of Civil Engineering and Management, 2013)
Analysis of various wood products tested under the exposure to 30 kW/m2, 35 kW/m2, 40 kW/m2, 45 kW/m2and 50 kW/m2 heat flows in accordance with LST ISO 5657:1999 “Reaction to fire tests – ignitibility of building products using a radiant heat source” was performed. Selected boards were subjected to reaction to fire tests in accordance with LST EN 13823:2010 “Reaction to fire tests for building products”. The tests were performed on 6 mm, 10 mm, 15 mm and 18 mm thick oriented strand boards (OSBs) and 24-mm thick wood particle boards (WPBs), both impregnated with BAK-1 fire retardant solution and non-impregnated. The average time to ignition (TTI) was determined. The impact of the impregnator on heat release rate, smoke formation and carbon dioxide (CO2) emission in the course of combustion of impregnated and non-impregnated OSB and WPB was studied. In the course of the research, statistical analysis was performed and empirical equations and their correlation coefficients were obtained. Conclusions were formulated at the end of the study.